PSIV-12 Effects of feeding a novel alfalfa leaf pellet product (ProLEAF MAX™) and alfalfa stems (ProFiber Plus™) on production of lactating dairy cows. (8th October 2021) - Smith, Laura A; Young, Allen Y; Pratt, Chris; Thornton, Kara J
Abstract: Alfalfa is a commonly grown forage in the Intermountain west and is often included in lactating dairy cow rations. This study investigated the effects of including novel alfalfa products: ProLEAF MAX™ (PLM), an alfalfa leaf pellet; and ProFiber Plus™ (PFP), alfalfa stems, in the diet of lactating dairy cows on dry matter intake, milk yield, and milk components. Holstein cows were housed in a freestall barn and milked in a free-flow automatic milking system. All cows were fed each treatment for 21-days, then switched to the next treatment utilizing a crossover experimental design. The five treatments were: control (CON, typical diet including alfalfa hay; n = 65); low-quality alfalfa hay (LQ+PLM, a diet that replaced alfalfa hay with low-quality alfalfa hay and PLM; n = 62); PLM+PFP (a diet that replaced alfalfa hay with PLM and PFP; n = 65); PLM (a diet that replaced alfalfa hay with PLM; n = 62); and PFP (a diet that replaced alfalfa hay with PFP; n = 60). Cows were group fed a partial mixed ration balanced for 40.8 kg milk, 3.9% milk fat and 3.3% milk protein. Individual milk yield and milk components were recorded daily by the automatic milking system. Dry matter intake was also recorded daily. When fed the PFP diet, cows had decreased (P < 0.01) dry matter intake compared to the other diets. Milk yield was increased (P < 0.01) when cows received the PLM diet when compared to the other diets. When fed the PFP and PLM+PFP diets, milk fat was increased (P < 0.01) when compared to the other diets. Milk protein was decreased (P < 0.01) when cows were fed the PFP diet when compared to the other diets. These data indicate that inclusion of fractionated alfalfa products in the diet of lactating dairy cows has the potential to increase milk yield and milk components.